Advancements in microemulsion-based fabrication of upconversion-mediated multifunctional materials - Zhang, Yi; Mei, Qingsong; Zhang, Zhen (Frontiers in Photonics, 2024)
Upconversion nanoparticles (UCNPs) have experienced significant advancements, finding applications in diverse fields over the past decade. The growing demand for UCNP-based nanoplatforms with multifunctionality to address complex scenarios has led to the emergence of the microemulsion confined self-assembly method, which allows for the integration of different UCNPs or UCNPs with additional functional materials within a single entity, resulting in a nanoplatform that possesses a wide range of properties suitable for specific applications. This comprehensive review aimed to summarize recent developments in the design of UCNP assemblies using the microemulsion confined self-assembly method, which focused on exploring their applications in critical areas such as color encoding, bioimaging, and programmable therapeutics. Furthermore, the review acknowledged the existing limitations associated with the microemulsion confined self-assembly method and provided an in-depth discussion of potential solutions to overcome these challenges, aiming to foster further progress and innovation in the design and application of UCNP assemblies.